Clinical management of comorbid diabetes and psychotic disorders. (May 2015) - Chwastiak, Lydia A; Freudenreich, Oliver; Tek, Cenk; McKibbin, Christine; Han, Jaesu; McCarron, Robert; Wisse, Brent
Summary Individuals with psychotic disorders experience substantial health disparities with respect to diabetes, including increased risk of incident diabetes and of poor diabetes outcomes (eg, diabetes complications and mortality). Low-quality medical care for diabetes is a significant contributor to these poor health outcomes. A thoughtful approach to both diabetes pharmacotherapy and drug management for psychotic disorders is essential, irrespective of whether treatment is given by a psychiatrist, a primary care provider, or an endocrinologist. Exposure to drugs with high metabolic liability should be minimised, and both psychiatric providers and medical providers need to monitor patients to ensure that medical care for diabetes is adequate. Promising models of care management and team approaches to coordination and integration of care highlight the crucial need for communication and cooperation among medical and psychiatric providers to improve outcomes in these patients. Evidence-based programmes that promote weight loss or smoking cessation need to be more accessible for these patients, and should be available in all the settings where they access care.